Enhancement of dielectric and energy density properties in the PVDF‐based copolymer/terpolymer blends. Issue 6 (7th April 2015) - Ullah, Amir; ur Rahman, Ata; Won Ahn, Chang; Rahman, Muneeb‐ur; Ullah, Aman; Rehman, Zia‐ur; Javid Iqbal, Muhammad; Kim, Ill Won
<x xml:space="preserve">Abstract</x> We investigated the high dielectric constant and energy storage density for the blends of P(VDF‐TrFE) copolymer and P(VDF‐TrFE‐CFE) terpolymer. The degradation of coercive field (Ec) and remnant polarization (Pr) of the copolymer under an electric field of 125 MV/m was observed and the copolymer changed into a typical relaxor ferroelectric with doping of terpolymer. The dielectric constant of P(VDF‐TrFE) was found to be ∼11, but was enhanced to ∼55 by blending with P(VDF‐TrFE‐CFE) at 60 wt%. Consequently, a higher energy density of about 4.2 J/cm3 was obtained in these blends in contrast to about 3.6 J/cm3 in the terpolymer at the very low applied electric field of 125 MV/m. These results demonstrate the promise of blend approaches for tailoring and enhancing the dielectric properties of ferroelectric polymers. POLYM. ENG. SCI., 55:1396–1402, 2015. © 2015 Society of Plastics Engineers